Long-Term Carbapenems Antimicrobial Stewardship Program - José Francisco García-Rodríguez; Belén Bardán-García; Pedro Miguel Juiz-González; Laura Vilariño-Maneiro; Hortensia Álvarez-Díaz; Ana Mariño-Callejo (MDPI AG, 2020)
Objective. To evaluate clinical and antibiotic resistance impact of carbapenems stewardship programs. Methods: descriptive study, pre-post-intervention, between January 2012 and December 2019; 350-bed teaching hospital. Prospective audit and feedback to prescribers was carried out between January 2015 and December 2019. We evaluate adequacy of carbapenems prescription to local guidelines and compare results between cases with accepted or rejected intervention. Analysis of antibiotic-consumption and hospital-acquired multidrug-resistant (MDR) bloodstream infections (BSIs) was performed. Results: 1432 patients were followed. Adequacy of carbapenems prescription improved from 49.7% in 2015 to 80.9% in 2019 (p < 0.001). Interventions on prescription were performed in 448 (31.3%) patients without carbapenem-justified treatment, in 371 intervention was accepted, in 77 it was not. Intervention acceptance was associated with shorter duration of all antibiotic treatment and inpatient days (p < 0.05), without differences in outcome. During the period 2015-2019, compared with 2012-2014, decreased meropenem consumption (Rate Ratio 0.58; 95%CI: 0.55-0.63), candidemia and hospital-acquired MDR BSIs rate (RR 0.62; 95%CI: 0.41-0.92, p = 0.02), and increased cefepime (RR 2; 95%CI: 1.77-2.26) and piperacillin-tazobactam consumption (RR 1.17; 95%CI: 1.11-1.24), p < 0.001. Conclusions: the decrease and better use of carbapenems achieved could have clinical and ecological impact over five years, reduce inpatient days, hospital-acquired MDR BSIs, and candidemia, despite the increase in other antibiotic-consumption.